THE IMPACT OF PHYSICAL ACTIVITY ON ENHANCING THE IMMUNE SYSTEM - Axtamov Djamshed Baxromovich (Web of Journals Publishing, 2025)
This paper examines the vital role of physical activity in strengthening the immune system. It outlines how regular, moderate exercise can boost immune function, improve the body’s defense against infections, and reduce inflammation. The study also explores the physiological mechanisms behind these benefits and highlights the importance of maintaining a balanced exercise routine to optimize immune health without causing strain or weakening the body’s defenses.
Keywords: Physical activity, immune system, immune health, inflammation reduction, infection prevention, exercise benefits, body defense, health promotion.